2022
DOI: 10.1017/pds.2022.135
|View full text |Cite
|
Sign up to set email alerts
|

Service Design Approach to Elevate the Patient Experience during Home X-Rays

Abstract: Healthcare services have evolved with advances in science, technology and societal needs. Despite being around for two decades, 'X-ray at Home' has seen limited adoption. Understanding its enablers and disablers can lead to insights to develop an accessible healthcare service ecosystem. Healthcare organisations have adopted design thinking to develop new products but healthcare service design is still in its introductory phase. This qualitative study describes the current state of home X-ray services in Mumbai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Design thinking considers three broad categories of touchpoints in services: physical, digital, and human touchpoints [118]. They all play an important role in the service process and are an important indicator of service experience [119]. As shown in Figure 5, in this study, service contact points can be summarized as: registration, information transparency, doctor communication and attitude, inspection and treatment environment, medicine collection and follow-up procedures, etc.…”
Section: Service Touchpoint Analysismentioning
confidence: 99%
“…Design thinking considers three broad categories of touchpoints in services: physical, digital, and human touchpoints [118]. They all play an important role in the service process and are an important indicator of service experience [119]. As shown in Figure 5, in this study, service contact points can be summarized as: registration, information transparency, doctor communication and attitude, inspection and treatment environment, medicine collection and follow-up procedures, etc.…”
Section: Service Touchpoint Analysismentioning
confidence: 99%
“…From the touchpoints, the user's preconceptions and perceptions are shaped, they are redirected, and their experience is defined about whether or not to use a service again. A study on the remote use of x-rays demonstrated how SD could improve service (Parikh & Shrivastav, 2022), and during the analysis, it was reported that healthcare organizations and providers have little experience in identifying touchpoints to understand the patient experience. Thus, SD can support how the elements of a service are related by understanding the interrelation of each touchpoint rather than viewing them as static relations.…”
Section: Using Service Design To Analyze Experiencesmentioning
confidence: 99%